Really good logos explained top design professionals critique 500 logos & explain what makes them work - Chase, Margo (Rockport Publishers, 2011)
A collection of 500 great logos critiqued by a panel of internationally acclaimed designers In Really Good Logos Explained, some of today's top creative minds critique and appraise over 500 examples of truly exceptional logos, and explain what makes them work.
Keywords: Logos (Symbols) -- Design; Corporate image; Branding (Marketing); Entreprises; Image; Stratégie de marque; corporate image; branding; Logos (Symbols); Design